X-raying the Hubble Frontier Fields cluster Abell 2744. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Eckert, Dominique
Abstract: Abell 2744 was the first HFF cluster completed. It displays a fascinating complexity in its distribution of dark and luminous matter, which led to its nickname of the Pandora cluster . In late 2014 we obtained a deep (110 ks) observation of this cluster with XMM-Newton, with the aim of making a detailed comparison between the optical, X-ray and lensing properties of this system. The new X-ray observation unveiled the presence of three hot gas filaments extending on scales of several Mpc and connected to the cluster core. The X-ray structures coincide spatially with the distribution of galaxies and dark matter and provide strong evidence for the existence of the elusive warm-hot intergalactic medium (WHIM). The new observation also reveals the complexity of the thermodynamic structure of the cluster core and a probable shock front associated with the radio relic located 1 Mpc NW of the cluster core.